Upaya Peningkatan Keterampilan Berpikir Kritis Peserta Didik Melalui Model Project Based Learning pada Materi Ekologi dan Keanekaragaman Hayati Indonesia - Nasra, Anisya Rahmaniah; Bastian, Norma; Salimatussa’diyah, Salimatussa’diyah (STKIP HARAPAN BIMA, 2025)
This study aims to improve students' critical thinking skills on Indonesian ecology and biodiversity material in class VII. This type of research is Classroom Action Research (PTK). This PTK is carried out by applying a project-based learning model as an action to improve students' critical thinking skills. The sample of this study amounted to 29 students. This research instrument is a critical thinking skills test instrument. The results showed an increase in each indicator of critical thinking skills from each cycle and classical completeness of students' critical thinking skills which initially 43% in cycle 1 increased to 82% in cycle 2. Therefore, it can be concluded that the project-based learning model is considered as an effective solution to improve students' critical thinking skills and based on the findings in this study, students' critical thinking skills that are improved through project-based learning meet the success criteria.